2018
DOI: 10.1177/1060028018786510
|View full text |Cite
|
Sign up to set email alerts
|

Ozenoxacin: A Novel Topical Quinolone for Impetigo

Abstract: Ozenoxacin, the first nonfluorinated quinolone, is a safe, topical treatment for impetigo in patients 2 months of age and older. Although clinical trials demonstrate efficacy compared with placebo, comparative trials to current treatment options are needed to identify its therapeutic use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…Ozenoxacin is a non-fluorinated quinolone with dual activity against bacterial gyrase and topoisomerase IV and currently used in the treatment of impetigo 76. It has excellent bactericidal activity against Methicillin-sensitive S. aureus, MRSA, MRSE, S. pyogenes, P. acnes and ofloxacin-resistant strains of S. aureus and S. epidermidis 77.…”
Section: Fluoroquinolonesmentioning
confidence: 99%
“…Ozenoxacin is a non-fluorinated quinolone with dual activity against bacterial gyrase and topoisomerase IV and currently used in the treatment of impetigo 76. It has excellent bactericidal activity against Methicillin-sensitive S. aureus, MRSA, MRSE, S. pyogenes, P. acnes and ofloxacin-resistant strains of S. aureus and S. epidermidis 77.…”
Section: Fluoroquinolonesmentioning
confidence: 99%
“…Ozenoxacin has bactericidal action against gram-positive organisms including MSSA (methicillin-sensitive Staphylococcus aureus), MRSA (methicillin-resistant Staphylococcus aureus), MRSE (methicillin-resistant Staphylococcus epidermidis), Streptococcus pyogenes, Propionibacterium acnes and ofloxacin-resistant strains of S. aureus and S. epidermidis. [19][20][21] The antibacterial activity of ozenoxacin has been found to be highly superior and the MIC lower, compared to other quinolones such as ofloxacin, nadifloxacin, and levofloxacin. 20 Ozenoxacin also been demonstrated to produce more rapid microbiological clearance compared to retapamulin, although the overall clinical efficacy at the end of treatment has been reported to be similar.…”
Section: Antimicrobial Spectrummentioning
confidence: 99%
“…Ozenoxacin (trade name Ozaenex/Xepi), developed by Ferrer International S.A., is a novel, non-fluorinated, topical quinolone that is bactericidal against many Gram-positive organisms, including MRSA, MSSA, MRSE and S. pyogenes [137]. In vitro, MIC 90 values against bacteria such as MSSA, MRSA, S. epidermis was between two- and >16,000-fold greater than compared to other commonly prescribed antibiotics, such as ofloxacin, levofloxacin, erythromycin and gentamicin [138].…”
Section: Novel Anti-gram-positive Antibioticsmentioning
confidence: 99%
“…In vitro, MIC 90 values against bacteria such as MSSA, MRSA, S. epidermis was between two- and >16,000-fold greater than compared to other commonly prescribed antibiotics, such as ofloxacin, levofloxacin, erythromycin and gentamicin [138]. Previous trials demonstrated a complete lack of systemic absorption and no formation of metabolites when ozenoxacin was applied topically, likely contributing to the absence of drug interactions [137]. As a result, the elimination of ozenoxacin has not been investigated in humans [139].…”
Section: Novel Anti-gram-positive Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation